Impact of Capital Structure on Firm Value with Profitability as Mediator: Indonesian Coal Companies Study - Singgih Widigdya; Akhmadi Akhmadi; Wawan Ichwanudin (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Over the past six years, global economic volatility shaped by geopolitical complexities has significantly impacted the coal sector, marked by fluctuating prices influenced by events such as the Ukraine crisis and the COVID-19 pandemic. This study focuses on Indonesian coal companies, examining the relationship between capital structure (DER), firm performance (ROA), and firm value (PBV). Through empirical analysis of 15 listed companies from 2018 to 2023, utilizing Hayes' Process Macro Model 4, the research finds that higher Debt to Equity Ratios (DER) negatively affect Return on Assets (ROA), indicating reduced efficiency in asset utilization. However, DER positively correlates with Price to Book Value (PBV), implying investor optimism regarding future earnings and asset worth. The study underscores the nuanced interplay between financial metrics in shaping corporate value within Indonesia's coal sector, offering insights for strategic financial management amid market uncertainties.